Permainan Edukatif untuk Meningkatkan Perilaku Pencegahan Demam Berdarah Dengue pada Siswa Pramuka Sekolah Dasar - Meuthya Aulia Dodhy Putri; Bagoes Widjanarko; Martini Martini (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2021)
Background: In 2016, the number of Dengue Hemorrhagic Fever (DHF) patients in Southeast Sulawesi has reported as much as 3,433 cases with IR 132.50 per 100,000 populations. The highest case incidence in Kendari reached 1,093 cases (IR = 372.80 per 100,000 population) with the highest cases in the age group 5-14 years reaching 44.9%. This study aims to examine the effect of snake-ladders modification game, as an educative game, for improving DHF prevention in terms of attitudes and behavior of scout students in elementary school.Method: The study is a quasi-experimental study with pretest-posttest group design by using purposive sampling. The subject is 50 students of Primary School Scouts in the working area of Puskesmas Poasia, Kendari City. Data was collected using a questionnaire and analyzed by Wilcoxon and Mann-Whitney tests.Results: There is an increase of knowledge (p < 0,001), attitudes (p < 0,001), and practices (p < 0,001) of primary school students in the prevention of DHF by providing educational game through snake-ladders modification. It recommends that educational game needs to be developed for health education in elementary students.